ANALISIS JUMLAH PRODUKSI OPTIMAL DALAM MEMPERLANCAR PENJUALAN (Studi kasus pada PT. Rumpun Sari Kemuning I, Kabupaten Karanganyar, Jawa Tengah) - Eka, Okky Kurniawati; Rhodiyah, Rhodiyah; Suryoko, Sri (Jurnal Ilmu Administrasi Bisnis, 2013)
Total production of the company is the dominant factor in influencing the sale of goods for the economical production can determine whether the goods sold in the market. Type of research used is descriptive. Analisys of the data used to determine method Economic Production Quantity (EPQ)the production optimal and economical expendirure. The purpose of this study was to determine the general optimal production level, the view of the cost, yield, production and availability of finished products of green tea. In particular, are (1) To determine the quantity of wet production for each production. (2) To determine the amount of the costs incurred in each production.(3) To determine the optimal production quantities according to the company. (4) To determine the optimal production quantities according to the EPQ. The analysis showed that production is determined from production wet dry, wet production quantities can be influenced by several factors such as the condition of shoots in the garden is not good for plant disease, climate and rainfall, and the availability timed. Levels rendement average is 22.40%. Rendement The higher the better, the percentage yield levels generated. Optimal production level achieved Economic Production, the most economical in the year 2011 according to the calculation method of EPQ Optimal month production level achieved by calculation EPQ company that in 2010 April 96.750 Kg at a cost of Rp 148.309.229.Â  From the analysis of the total costs incurred where companies show a greater value than the sum of the cost of reckoning EPQ. Suggested EPQ method is used, as it will result in optimal production with minimum expenses. The Company takes into account the results of the product with the sale of product inventory that needs can be met.